Increasing Economic Efficiency of Producing Wheat in the West Siberia and South Ural as a Factor of Developing Import Substitution - Dmitry Sergeevich Nardin; Igor Aleksandrovich Bobrenko; Natalya Viktorovna Goman; Ekaterina Andreevna Vakalova; Svetlana Aleksandrovna Nardina (International Review of Management and Marketing, 2016)
The goal of the conducted research is to define top priority areas of increasing the economic efficiency of the wheat production as a factor of developing import substitution in the cereal sector. In order to achieve the set goal, the following tasks were determined and solved: the necessity to develop import substitution in the cereal sector for separate macro-regions of the Russian Federation were analyzed; possible areas of increasing the economic efficiency of wheat production were analyzed, the potential of increasing the efficiency of wheat production on the basis of the technology intensification by using micro fertilizers was defined; and the economic effect from using micro fertilizers when producing wheat and its impact on the development of import substitution in the sector were defined. The conducted research demonstrated the economic efficiency of the development of import substitution in the cereal sector of regions of the West Siberia and South Ural on the basis of the intensification of the technology of wheat production by means of implementing new breeds of local selection and applying micro fertilizers. In spite of the fact that the obtained economic effect is predicted, these calculations are confirmed by a number of the experiments made by the authors. As a whole, they stipulate the development of the described areas of import substitution. Further researches in this area anticipate the analysis and improvement of organizational and economic issues related to increasing the efficiency in the cereal sector, including the improvement of the system related to managing business processes that take place both on the macro-economic level in the agroindustrial complex of regions and on the level of separate agricultural goods producers. Implementation of measures focused on improving the system of managing operational business processes can give a serious economic effect due to revealing and involving hidden reserves into the economic turnover.